2016
DOI: 10.1080/10926488.2016.1150759
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Metaphor and Metonymy in Advertising: A Corpus-Based Account

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 15 publications
1
26
0
3
Order By: Relevance
“…there now is a wealth of evidence that gets at the conceptual nature of metaphor, including evidence from metaphors in gesture (Casasanto & Jasmin, 2010;Cienki & Müller, 2008;Walker & Cooperrider, 2016;Winter, Perlman, & Matlock, 2014), and from metaphors in pictures, adverts, and movies (Forceville, 2006(Forceville, , 2008Forceville & Urios-Aparisi, 2009;Ortiz, 2011;Pérez-Sobrino, 2016;Winter, 2014).…”
Section: Conceptual Metaphor Theorymentioning
confidence: 99%
“…there now is a wealth of evidence that gets at the conceptual nature of metaphor, including evidence from metaphors in gesture (Casasanto & Jasmin, 2010;Cienki & Müller, 2008;Walker & Cooperrider, 2016;Winter, Perlman, & Matlock, 2014), and from metaphors in pictures, adverts, and movies (Forceville, 2006(Forceville, , 2008Forceville & Urios-Aparisi, 2009;Ortiz, 2011;Pérez-Sobrino, 2016;Winter, 2014).…”
Section: Conceptual Metaphor Theorymentioning
confidence: 99%
“…While some studies have investigated viewers’ responses to multimodal metaphors (Pérez-Sobrino et al, 2018; Van Mulken et al, 2010), a few others have carried out quantitative analyses on the actual multimodal metaphors represented. Pérez-Sobrino (2016) collected 210 advertisements of goods, services and NGOs, and examined the prevalence of metaphor and metonymy as well as the modes used by the advertisers. She concluded that the preference for metaphtonymy in advertisements reflected the recent trend of producing minimalistic advertisements for easier comprehension and that visuals have a higher evocative potential than text.…”
Section: Metaphors In Visual Communicationmentioning
confidence: 99%
“…In the past decade, scholars working on figurative language in multimodal communication (e.g. Forceville and Urios-Aparisi, 2009; Hidalgo Downing and Kralievic, 2011; Pérez-Sobrino, 2016) have addressed the advantages of using metaphor in advertising. In the field of marketing, scholars have shown that metaphorical advertisements are more effective, i.e.…”
Section: Visual Metaphors and The Senses In Advertisingmentioning
confidence: 99%
“…Bolognesi et al, in press; El Refaie, 2003; Forceville, 1996, 2009, 2012; Phillips and McQuarrie, 2004; Šorm and Steen, 2013). Despite the increasingly large body of literature on visual metaphors, research on specific types of metaphors and other figures of speech within the visual mode is still limited (with the exception of metonymy, for which several recent studies are available, see for example Feng, 2017; Pérez-Sobrino, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%